2014
DOI: 10.1111/1751-2980.12152
|View full text |Cite
|
Sign up to set email alerts
|

Value of the patency capsule in pre‐evaluation for capsule endoscopy in cases of intestinal obstruction

Abstract: PC may be of diagnostic value in confirming the patency of the GI tract before capsule endoscopy. The routine use of PC might eliminate the contraindication of capsule endoscopy in many cases of intestinal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The first prospective feasibility study of PC was reported by Spada et al . The efficacy of PC has been reported …”
Section: Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…The first prospective feasibility study of PC was reported by Spada et al . The efficacy of PC has been reported …”
Section: Pcmentioning
confidence: 99%
“…73 The first prospective feasibility study of PC was reported by Spada et al 71 The efficacy of PC has been reported. 67,71,[73][74][75][76] 36 with permission. Omni mode compares the target image with reference image A and analyzes the areas of the target image covered by reference image A.…”
Section: Pcmentioning
confidence: 99%
“…This is a dissolving capsule (the same size and shape as the capsule endoscope) containing a radiofrequency tag. Failure to detect the radio frequency signal using a handheld scanner 30 h after ingestion suggests functional patency of the GI tract and predicts uncomplicated excretion of the capsule 18 19Cautions and contraindications to small bowel capsule endoscopy

Crohn's disease

Prolonged non-steroidal anti-inflammatory drug use

Severe abdominal pain or obstructive sounding symptoms

Previous abdominopelvic radiotherapy

Altered upper gastrointestinal anatomy

Dysphagia

…”
Section: Practical Considerationsmentioning
confidence: 99%
“…According to an analysis of published cases of suspected small bowel stricture, in which 203 patients were included, the patency capsule has a very high sensitivity (97%) and a specificity (83%) of confirming the patency of the gastrointestinal tract before videocapsule endoscopy examination [20]. Importantly, it is not a risk-free procedure, as there have been reported cases of temporary intestinal occlusion and in a study conducted on 22 patients evaluating the usefulness of the patency capsule in patients with suspected small bowel stenosis, 3 patients had intestinal occlusion which required emergency surgery in 2 [21].…”
Section: Discussionmentioning
confidence: 99%